Simple dreams [large type] : a musical memoir - Ronstadt, Linda (Center Point Large Print, 2013)
Singer Linda Ronstadt weaves together a memoir of her origins in Tucson, Arizona, her rise to stardom in the Southern California music scene of the 1960s and '70s, and the eclectic journey that led to her long-lasting success, including stories behind many of her beloved songs.